Kritik Sosial Terhadap Praktik Pendidikan Dalam Film â€œLaskar Pelangiâ€ - Nanang Martono (Jurnal Pendidikan dan Kebudayaan, 2010)
This article is an analysis of the criticisms of the practice of education in Indonesia. This criticism is based on the storyline presented in the â€œLaskar Pelangiâ€ (LP) movie. This article aims to analyze the essence of the LP movie seen through the sociologycal perspective. The essence of the film is more focused on social criticism conveyed through this film. Theoretically, education has two conflicting functions. According to the functional perspective, the positive function of education are transmit values across generations. Instead, the conflict perspective to explain that education actually leads to social inequality. More symbolic interactionism perspective see how the actors involved in the education process related to each other. Some of the criticism is delivered in between the formal education process that leaves the essence of education itself, the exclusivity of school functions, the formalization of education, inequality of access to education for lower-class society that cause social inequality, educational autonomy have not fully autonomous and the dichotomy of your favorite school and favorite. These conditions that characterize the dynamics of ational education so far has led to social inequality.